Total Loss in State Losses: Is it Really Only Caused by Fictitious Elements, and Useless? - Khusnul Khotimah Margawati; Harti Budi Yanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research seeks to clarify how the total loss method is applied in calculating state financial losses. The study is grounded in the principle that such losses must be actual and definite. State financial losses are crucial because they serve as a material element in proving corruption offenses. While various methods exist to calculate these losses, there is no standardized approach, and they cannot be universally applied. One commonly used approach is the total loss method. This study employs a qualitative methodology with a single case study design focused on the PT Timah Tbk case. It draws on secondary sources, including court ruling No. 70/Pid.Sus-TPK/2024/PN.Jkt.Pst., as well as in-depth interviews supported by data triangulation. The findings show that in the PT Timah Tbk case, the financial losses to the state meet the criteria of being actual and definite. The use of the total loss method was justified not only due to fictitious or unusable work or activities, but also due to the involvement of illegal goods or activities in the case.